Dos especies nuevas de los géneros Nevillea y Mikhailovella - Cózar, Pedro (Coloquios de Paleontología, 2001)
Two new endemic species from the Guadiato Area are described in this work, Nevillea cordobensis and Mikhailovella fresnedosensis. These species range from the Late Viséan foraminiferal zones 14 to 15 (V3a V3bα-β-γinf o Cf5 Cf6α-β-γ inf). The first occurrence of Mikhailovella from Zone 14 is controversial, because its first occurrence is usually used as biomarker from Zone 15. Analysis of the rest of the foraminiferal assemblages from the same levels also suggests that the first occurrence of this genus is at the base of the Late Viséan.